The Implementation of Picture Word Inductive Model (PWIM) in Writing Skill at SMPN 6 - Zam Zam, Himami Bulqiyah; Khodijah, Siti (Critical Review of English-Arabic World Journal, 2025)
Writing is a vital language skill closely connected with listening, speaking, and reading. One effective strategy to enhance writing ability is the Picture Word Inductive Model (PWIM), developed by Joyce, Weil, and Calhoun. PWIM combines writing and reading by using inductive reasoning to link words with images. To boost students’ motivation in learning English writing, teachers must select creative and effective teaching methods. The right strategy makes it easier for teachers to deliver material and helps students grasp the content more effectively. This research aims to explore the implementation of PWIM in teaching writing to eighth-grade students of SMPN 6 Situbondo, specifically Class A with 24 students. A descriptive qualitative method was used, with data collected through observations, interviews, and document analysis. Data validation was ensured through source and technique triangulation. The findings reveal four key aspects of PWIM implementation: the objectives of PWIM, the materials used, the steps in its application, and the evaluation of its impact on students’ writing skills